O tempo trem e sua estrada de ferro: a investigação de um mundo narrado sobre as ferrovias - Barroso, Roberta Filizola Custódio (2023)
This work arises during the elaboration of an animation called Tempo Trem, based on Ponta de Areia, song made by Milton Nascimento and Fernando Brant, which talks about a town, as so many others, abandoned by the side of the railroad after the end of the railways in Brazil. I related the repertoire of these musicians, especially the song already mentioned, with my mother's railway memories, to formulate the pre-production of the animated short film, my object of study. Throughout the process, I gathered railway memories, present in cinema, in literature, in Reis (2008), and in the interviews I did, in order to make both the film and this written work, composed of essays on subjects crossed by the railroads. Immersed in the narratives about the railroad, I aim to understand the development process of the plot of this short film and show how it tangents and expresses places, movements and knowledge, allowing access to the social and cultural experience of a collective imaginary. As a methodology for my creative journey and for the organization of the stops and Stations herein, I pilgrimaged in the form of improvisation and longitudinally integrated knowledge production, defined by Ingold (2012; 2015), with which I constituted my creative journey. Each of these Stations was built from a seam between fiction and concepts such as modernity (Berman, Benjamin, Hardman) and memory (Nora, Portelli), in addition to the approach with images raised by literature (Calvino, Rego, among others). Moreover, to conduct the interviews, I maintained "conscious subjectivity" for a subject-focused research, a methodology advocated by Kilomba (2019). In the end, I state that, besides presenting itself as a short film logbook, the present work develops memory and history subjects, with fiction as its main guide.